2001
DOI: 10.1038/modpathol.3880459
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Lung Tumors: Grade Correlates with Proliferation but not Angiogenesis

Abstract: Angiogenesis has been implicated in the progression of human neoplasia from benign precursor to invasive and metastatic phenotypes. The acquisition of dominant oncogenes in preneoplastic cells in vitro and in vivo has been associated with the increased ability of tumor cells to secrete angiogenic mediators and recruit blood vessels. However, in a subset of benign lesions, high levels of angiogenesis have been found before the conversion to invasive and metastatic phenotypes. In many of these benign lesions, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 34 publications
2
28
1
1
Order By: Relevance
“…Similarly, in the literature, thymic carcinomas and high-grade pulmonary neuroendocrine neoplasms tended to have a high rate of cellular proliferation, whereas thymomas and bronchopulmonary carcinoids had lower rates of cellular proliferation. 17,22,23,34,37,41,[43][44][45][46][47][48] This finding is in keeping with the observation in other thymic neoplasms that proliferative activity is linked with overexpression of p53 protein, particularly in more aggressive histologic grade tumors. 23,25 However, we found that low-grade thymic neuroendocrine tumors, which morphologically resembled typical carcinoid tumors, did not have the low labeling indices that we had previously reported in their low-grade pulmonary counterparts.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, in the literature, thymic carcinomas and high-grade pulmonary neuroendocrine neoplasms tended to have a high rate of cellular proliferation, whereas thymomas and bronchopulmonary carcinoids had lower rates of cellular proliferation. 17,22,23,34,37,41,[43][44][45][46][47][48] This finding is in keeping with the observation in other thymic neoplasms that proliferative activity is linked with overexpression of p53 protein, particularly in more aggressive histologic grade tumors. 23,25 However, we found that low-grade thymic neuroendocrine tumors, which morphologically resembled typical carcinoid tumors, did not have the low labeling indices that we had previously reported in their low-grade pulmonary counterparts.…”
Section: Discussionsupporting
confidence: 83%
“…23,25 However, we found that low-grade thymic neuroendocrine tumors, which morphologically resembled typical carcinoid tumors, did not have the low labeling indices that we had previously reported in their low-grade pulmonary counterparts. 48 The high proliferation rate that frequently occurs in thymic neuroendocrine tumors could be a key factor in explaining its aggressive biological behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There were three cases of smallcell lung cancer with a low percentage of Ki-67 expression level (below 30 %) in the present study. Even though some studies showed a high Ki-67 percentage in small-cell lung cancers [34,35], other studies showed small-cell lung cancer cases with a low percentage of Ki-67-positive cells [36,37]. Therefore, we considered the findings in the present study reliable.…”
Section: Discussionmentioning
confidence: 61%
“…Both large-cell neuroendocrine carcinomas and smallcell carcinomas demonstrated significantly higher proliferation activity than typical and atypical carcinoids (Po0.0001), and the same was true for atypical carcinoids than typical carcinoids (Po0.01), while there was no significant difference in Ki-67 expression between large-cell neuroendocrine carcinomas and small-cell carcinomas (P ¼ 0.4031), in keeping with previous studies. 34,35 These results reflect the low-grade biological features of typical carcinoid, the less aggressive behavior of atypical carcinoid and the highly malignant nature of large-cell neuroendocrine carcinoma and small-cell carcinoma.…”
Section: Discussionmentioning
confidence: 61%